Implementation of Non Pharmacological Therapy with Tomato Juice to Reduction High Blood Pressure in Elderly With Hypertension - Supriadi, Dedi; Maryana, Elsa (Jurnal Vocational Nursing Sciences (VNUS), 2024)
Introduction: Hypertension or often called high blood pressure is a disorder of the circulatory system that causes blood pressure to increase to above the normal limit of 140/90 mmHg. Hypertension is a degenerative disease like diabetes mellitus which can attack anyone at a young or old age. Apart from that, hypertension is also a non-communicable disease but is still a global problem. The prevalence of hypertension cases in Indonesia is 63,309,620 people, while the death rate in Indonesia due to hypertension is 427,218 deaths. Patients with hypertension may benefit from non-pharmacological and pharmaceutical management interventions. Because 100 grams of tomatoes contain 100 grams of calories, 1 gram of protein, 4.2 grams of carbohydrates, 5 mg of calcium, 360 mg of potassium, 0.5 mg of iron, 40 mg of vitamin C, 1500 IU of vitamin A, 06 mg of vitamin B, and 94 g of water, tomatoes have the potential to lower blood pressure. Objective: The aim of this case study is to carry out nursing care for elderly people with hypertension problems and to see the effect of implementing tomato juice therapy to help lower blood pressure. Method: The method used is descriptive using a case study approach with the subject used as case study material being an elderly patient who has hypertension problems with a knowledge deficit. Patient and family data collection techniques include assessment stages, interviews, observation, physical examination, and also documentation studies. Results: Knowledge deficit nursing diagnosis related to lack of exposure to information with diagnosis number D.0111, given tomato juice intervention for 3 days by consuming tomato juice twice a day, after the intervention was carried out, the patient's nursing problem was resolved with a marked decrease in blood pressure from 160/ 100 mmHg drops to 150/90 mmHg. Conclusion: Providing tomato juice intervention has proven to be effective in helping reduce high blood pressure in hypertension sufferers. The benefits of this non-pharmacological therapy will be maximized if done regularly.